Peran Pemuda Dalam Pengembangan Pemasaran Digital Terhadap UMKM Desa Sidomulyo - Bahtiar, Yuyun; Ma’arif, Iin Baroroh; Afidah, Nurul; Nur, Luluk Choirun Nisa; Agustina, Ulfa Wulan (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2024)
Digital marketing has become a main pillar in advancing micro, small and medium enterprises (UMKM) in various regions, including in Sidomulyo Village, Megaluh District, Jombang Regency. This study aims to analyze the role of youth in supporting and developing digital marketing for MSMEs in Sidomulyo Village, Megaluh District, Jombang Regency. This study uses qualitative methods with interview, observation, and documentation study techniques. The results of this study underline the importance of the youth's role in driving digital transformation in rural environments. Youth are not only agents of change, but also the main drivers in increasing income and welfare of Sidomulyo Village MSMEs, Megaluh District, Jombang Regency through digital marketing. Therefore, it is necessary to continue encouraging the active role of youth in supporting and developing digital marketing for MSMEs, with support from various parties, including the government, non-governmental organizations, and the private sector.